Gearing up for genome-wide gene-association studies. - Farrall, M; Morris, A (2005)
One of the grand challenges of human genetics to systematically map by gene-association susceptibility genes for complex diseases is underway. High-throughput genotyping platforms have been developed; a comprehensive map of human genetic variation (HapMap) to guide efficient marker selection is imminent and many researchers have assembled suitable cohorts of patients. Expectations are understandably high and it is timely to review the promise and pitfalls of this strategy.